On-demand quality management for service-oriented architecture initiative: A conceptual study - Sulong, Muhammad Suhaizan; Abdullah, Noraswaliza; Emran, Nurul Akmar; Abdul Aziz, Azlianor (RSIS International, 2024)
In the real world, service-oriented architecture (SOA) is a part-technology and part-business venture. Both parts play an important role in making SOA initiatives a reality for organisations to become SOA-enabled. The incorporation of technology and business is to respond to the needs of agile organisations and increase technological advancement. Organisations implementing SOA initiatives are able to architect business processes, functions and structures with recent technology enhancement specifically in services and composite applications. A comprehensive literature review on the SOA initiative has evolved significantly over recent decades, highlighting that while SOA effectively transforms organisational operations by aligning technology and business, there are documented failures in the implementation of SOA initiatives. The focus on this issue needs to be addressed despite a few studies found in the literature, both in the academic and business areas, covering the SOA initiative. The failure of SOA initiatives is attributed to the use of low-quality information (IQ) and the lack of verification through appropriate IQ management systems. These findings culminated in the formulation of a conceptual framework that combines SOA initiative with IQ management, shedding light on experiences among SOA team members. It shows a clear necessity to establish further work on case studies as well as in the comparative analysis to comprehend the implications of the results obtained. In this context, it is crucial that SOA initiatives with managing IQ will enhance organisational performance throughout the entire implementation of the SOA initiative.